PEMBERDAYAAN PETANI DALAM PENANGKARAN BIBIT KARET BER-Trichoderma sp SEBAGAI UPAYA PENGENDALIAN PENYAKIT JAMUR AKAR PUTIH - Dewi Rezki; Siska Efendi; Ade Noverta; Edwin Edwin; Yulistriani Yulistriani; Wulan Kumala (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2018)
Abstract The lecturers and community-based science and technology service activities are carried out as an effort  to control white root fungal disease caused by Rigidiporus microporus or Rigidoporus lignosus which is difficult to control by farmers because it attacks the root system of rubber plants. One effort that can be done to control this JAP disease is the application of Trichoderma sp in the nursery of rubber plants, so that the rubber seedlings that will be planted fries have been protected by Trichoderma sp. The partner in this service activity is the True Nursery Breeder farmer group which is a group of rubber seed breeder farmers. Farmers are trained to be able to propagate Trichoderma sp and utilize agricultural waste into compost using Trichoderma sp as a decomposer. This activity was held in Kenagarian Sungai Dareh, Pulau Punjung District, Dharmasraya Regency. The result of this activity is that the farmers succeeded in propagating Trichoderma sp using bran as a growing medium, farmers have also made compost from agricultural waste around their environment. After isolating the soil of rubber seed media that has been applied Trichoderma sp, it is known that Trichoderma sp successfully grows well in the soil media and the root system of rubber seedlings. Thus, farmers have been able to do nurseries usingTrichoderma sp as an initial effort to overcome the attacks of white root fungus. Rubber seeds with Trichoderma sp, compost and Trichoderma sp produced by the True Nursery breeders have been marketed to farmers and the community around Kenagarian Sungai Dareh, so that this activity can help improve the welfare of farmers.